342 Impact of temporary traffic bans on the risk of acute coronary syndromes in a large metropolitan area. (17th December 2020) - De Luca, Alessandra; Proietti, Igino; Trani, Carlo; Berni, Andrea; Sergi, Sonia Cristina; Speciale, Giulio; Tanzilli, Gaetano; Tomai, Fabrizio; Di Giosa, Alessandro; Marchegiani, Giada; Zoccai, Giuseppe Biondi; Versaci, Francesco
Abstract: Aims: Strong epidemiologic evidence has highlighted the role of pollution, on top of adverse climate features, as a novel cardiovascular risk factor. However, mechanistic proof that reducing pollution may be beneficial to prevent atherothrombotic events is limited. We aimed at appraising the impact of temporary traffic bans in a large metropolitan area on the risk of acute coronary syndromes. Methods and results: Aggregate and anonymized data from 15 tertiary cardiac care centers were obtained detailing pre-coronarivus disease 2019 (COVID-19) daily cases of ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction (NSTEMI), including those treated with percutaneous coronary intervention (PCI). Data on pollutants and climate were sought for the same days. Mixed level regression was used to compare the week before vs. after the traffic ban (Fortnight analysis), the 3 days before vs. after (Weekly analysis) and the Sunday before vs. after (Sunday analysis). A total of 8 days of temporary traffic bans were included, occurring between 2017 and 2020, totaling 802 STEMI and 1196 NSTEMI in the Fortnight analysis, 382 STEMI and 585 in the Weekly analysis, and 148 STEMI and 210 NSTEMI in the Sunday analysis. Fortnight and Sunday analysis did not disclose a significant impact of traffic ban on STEMI or NSTEMI (all P  > 0.05). Conversely, Weekly analysis showed non-significant changes for STEMI but a significant decrease in daily NSTEMI when comparing the 3 days before the traffic ban with the ban day ( P  = 0.043), as well as the 3 days before vs. the 3 days after the ban ( P  = 0.025). No statistically significant effect of traffic ban was found at Fortnight, Weekly or Sunday analyses for daily mean concentrations of benzene, carbon monoxide, nitric oxide, nitrogen dioxide, ozone, sulfur dioxide, particulate matter (PM) <2.5 µm or PM < 10 µm (all P  > 0.05). However, minimum daily concentrations showed a significant reduction of ozone during the ban in comparison to the week preceding it ( P  = 0.034), nitric oxide during the ban in comparison to the 3 days preceding it ( P  = 0.046), and an increase in benzene during the ban in comparison to the Sunday before ( P  = 0.039). Conclusion: Temporary traffic bans may favorably reduce coronary atherothrombotic events, and in particular NSTEMI, even if not globally and immediately impacting on environmental pollution. Further controlled studies are required to confirm and expand this hypothesis-generating results.